Report on Candidates' Work in the Secondary Education Certificate General and Basic Proficiency Examinations: Typewriting - Caribbean Examinations Council (Caribbean Examinations Council (CXC), 1989)
This report contains general and specific comments on the performance of candidates in June 1989 Caribbean Secondary Education Certificate Examination (CSEC) in Typewriting at the general and basic proficiency.
Keywords: Typewriting; CSEC